The association of Cryptosporidium from three different points of Balok River and Kuantan River by using physico-chemical and heavy metal assessments - Zainutdin, Fatin Khairunnisa; Barudin, Mohd Aiman; Jainul, Mohammed Abdullah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Hainan Medical University, 2017)
Objective: The objectives of this study were to detect the occurrence of Cryptosporidium oocysts and to assess the physico-chemical and heavy metal parameters in two main rivers in Kuantan. Methods: Water samples were collected at three sampling points per river (upstream, midstream, downstream) from Kuantan River and Balok River. Samples were filtered using the Continuous Flow Centrifugation (CFC) machine followed by immunomagnetic separation technique to isolate Cryptosporidium oocysts and stained using fluorescein isothiocyanate (FITC) –staining. Cryptosporidium oocysts were examined using fluorescence microscope. Physical parameters were assessed in-situ using Cyber Scan PCD 650 multi-parameter instrument. Both chemical and heavy metal assessment were done in the laboratory following the American Public Health Association (APHA) Standard Method with slight modification. The parameters attained were compared with the Interim National Water Quality Standards (INWQS) which is the standard vital parameters used to evaluate the safety level of surface water in Malaysia. Results: All samples were positive with Cryptosporidium oocysts. Results for physical parameters were within the range of Interim National Water Quality Standards (INWQS) in Malaysia. For chemical assessment, results for chemical oxygen demand and biological oxygen demand exceeded the INWQS range in most of the sampling points. Of 23 metal elements assessed, only 9 elements were found. Both Kuantan River and Balok River can be classified under Class III river following INWQS which requires extensive treatment. Conclusions: This study hoped to provide new and updated information on the occurrence of Cryptosporidium and its physico-chemical assessment in two main rivers in Kuantan. Future study on molecular identification of Cryptosporidium in rivers needs to be done in order to identify the source of transmission of this waterborne parasite.